Metaphor Studies Investigation in Mathematics Education: A Systematic Review - Ilham Falani; Yetti Supriyati; Jefri Marzal; Dewi Iriani; Gugun Manosor Simatupang (Indonesian Journal of Mathematics Education, 2023)
Metaphor is a powerful cognitive tool to understand or develop mathematical concepts. Although metaphor has been progressively recognized in mathematics education, there is an inadequate systematic review of its application and achievement. Therefore, this study aims to investigate and map metaphors studies trends in mathematics education. Data were collected from a systematic review of 70 metaphor studies in mathematics education published from 2012–2021 using the PRISMA guidelines. The results showed the mapping of the metaphor studies' attributes in mathematics education. Future research can use this information as the basis for determining the novelty of research related to metaphors. Furthermore, they can use this information to determine its potential and opportunities for future research. The primary limitation of this review is related to the sensitivity of the search strategy, which makes it impossible to cover relevant studies comprehensively.